2016
DOI: 10.1021/acsami.5b12523
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Fenton Reactors as a New Class of Oxidative Stress Amplifying Anticancer Therapeutic Agents

Abstract: Cancer cells, compared to normal cells, are under oxidative stress associated with an elevated level of reactive oxygen species (ROS) and are more vulnerable to oxidative stress induced by ROS generating agents. Thus, manipulation of the ROS level provides a logical approach to kill cancer cells preferentially, without significant toxicity to normal cells, and great efforts have been dedicated to the development of strategies to induce cytotoxic oxidative stress for cancer treatment. Fenton reaction is an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 40 publications
0
77
0
Order By: Relevance
“…However, it has also been suggested that, with successful specific targeting, the production of ROS at a desired target (i.e. cancer cellswhich are more sensitive to ROS) can be therapeutically advantageous, enhancing cancer cell death (Kwon et al 2016). NPs may also escape a degradative fate if they are recycled back to the plasma membrane in Rab11 positive compartments or if they are released from the endo-lysosomal system into the cytoplasm (Ullrich et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been suggested that, with successful specific targeting, the production of ROS at a desired target (i.e. cancer cellswhich are more sensitive to ROS) can be therapeutically advantageous, enhancing cancer cell death (Kwon et al 2016). NPs may also escape a degradative fate if they are recycled back to the plasma membrane in Rab11 positive compartments or if they are released from the endo-lysosomal system into the cytoplasm (Ullrich et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic PolyCAFe conjugates benzoyloxy CA and iron-containing compounds in its skeleton and self-assembles to form micelles which generate cytotoxic hydroxyl radicals that preferentially kill cancer cells. 43 In addition, nanoparticles designed to incorporate CA in its pH-sensitive hydrophobic backbone via acid-cleavable acetal linkages and encapsulate CPT, which induced apoptotic cell death through the generation of intracellular ROS and their apoptotic activities were significantly enhanced with a payload of CPT and have been used in in vitro and in vivo model of SW 620 colon tumor-bearing mice. 44 However, their uptake by cells, biodistribution, safety and toxicity pharmacokinetics in normal tissues and organs were not thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning above‐mentioned issues, upconversion nanoparticles (UCNPs) have received much attention due to the capability of converting longer wavelength irradiation (NIR) into the shorter wavelength light (UV or visible light) . Based on this character, on account of multiphoton absorption of NIR light, Yb/Tm‐codoped UCNPs can be used as an efficient UV–vis source, triggering PDT effect and toxic •OH to kill cancer cells . In addition, the UCNPs containing Yb or Gd could be served as excellent CT contrast agents owning to their high atomic and strong X‐ray attenuation, which are of great significant for cancer diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41] Based on this character, on account of multiphoton absorption of NIR light, Yb/Tm-codoped UCNPs can be used as an efficient UV-vis source, triggering PDT effect and toxic •OH to kill cancer cells. [42][43][44][45][46][47] In addition, the UCNPs containing Yb or Gd could be served as excellent CT contrast agents owning to their high atomic and strong X-ray attenuation, which are of great significant for cancer diagnosis. [2,[48][49][50][51] Therefore, Yb/Tmcodoped UCNPs were the optimal choice for cancer diagnosis and UV source activating PDT effect of ZnFe 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%